Engineered IscB-ωRNA system with improved base editing efficiency for disease correction via single AAV delivery in mice - Ruochen Guo; Xiaozhi Sun; Feizuo Wang; Dingyi Han; Qiaoxia Yang; Hua Gao; Zhifang Li; Zhuang Shao; Jinqi Shi; Rongrong Yang; Xiaona Huo; Junda Yan; et al. (Cell Reports)
Summary: IscBs, as hypercompact ancestry proteins of Cas9 nuclease, are suitable for in vivo gene editing via single adeno-associated virus (AAV) delivery. Due to the low activity of natural IscBs in eukaryotic cells, recent studies have been focusing on improving OgeuIscB’s gene editing efficiency via protein engineering. However, in vivo gene editing efficacy of IscBs for disease correction remained to be demonstrated. Here, we showed effective gene knockout and base editing in mouse embryos. To further improve IscB activity, we performed systematic engineering of IscB-associated ωRNA and identified a variant, ωRNA∗-v2, with enhanced gene editing efficiency. Furthermore, our study demonstrated the efficacy of an engineered IscB-ωRNA system for robust gene knockout and base editing in vivo. Single AAV delivery of IscB-derived cytosine and adenine base editors achieved disease correction in a mouse model of tyrosinemia. Therefore, our results indicated the great potential of miniature IscBs for developing single-AAV-based gene editing therapeutics.